2019
DOI: 10.1039/c9dt00926d
|View full text |Cite
|
Sign up to set email alerts
|

Role of His63 in HutZ fromVibrio choleraein the heme degradation reaction and heme binding

Abstract: His63 of HutZ from Vibrio cholerae does not contribute to regioselectivity of heme degradation but plays a key role in maintaining the orientation of subunits for HutZ to function in heme degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Recent studies by our group further showed that subunit-subunit interactions play a key role in the heme degradation reaction [16]. The distance between heme and Trp109, which reflects subunit-subunit orientational changes, was increased from [16][17][18] Å for wild-type HutZ to 23-25 Å for R92A and R92L mutant enzymes, similar to data obtained for mutants of Ala31 [16], His63 [19] and Asp132. Based on the collective results, we propose an activation mechanism of HutZ involving conformational changes at Arg92, which are transmitted to the heme axial ligand His170 through Ala31, His63, and Asp132, with modulation of subunit-subunit interactions.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Recent studies by our group further showed that subunit-subunit interactions play a key role in the heme degradation reaction [16]. The distance between heme and Trp109, which reflects subunit-subunit orientational changes, was increased from [16][17][18] Å for wild-type HutZ to 23-25 Å for R92A and R92L mutant enzymes, similar to data obtained for mutants of Ala31 [16], His63 [19] and Asp132. Based on the collective results, we propose an activation mechanism of HutZ involving conformational changes at Arg92, which are transmitted to the heme axial ligand His170 through Ala31, His63, and Asp132, with modulation of subunit-subunit interactions.…”
Section: Introductionsupporting
confidence: 80%
“…Changes of the subunit-subunit interactions also occurred in the His63 mutant [19]. His63 is presumed to be located close to heme and in the same subunit containing Asp132 but a different subunit from His170 and Arg92 (Supplemental Fig.…”
Section: Regulatory Mechanisms Of Heme Degradation By Hutzmentioning
confidence: 95%
See 1 more Smart Citation
“…Many bacterial HOs have been characterized and the majority are structurally similar to mammalian HOs . Typically, HOs oxidatively cleave heme at the α‐ meso position to afford biliverdin IXα, CO, and Fe 2+ ; however, cleavage has been observed at all four meso positions (Figure A) . HOs as well as heme‐degrading/cytoplasmic heme‐binding (HemS) proteins with no sequence homology to canonical HOs have been reported in multiple species of bacteria.…”
Section: Figurementioning
confidence: 99%
“… A) Example of heme degradation into biliverdin IXα by a heme oxygenase . Cleavage has been observed at the β‐, δ‐, γ‐ meso positions across nature. B) Gene organization of heme/siderophore utilization operon from E. anophelis Ag1.…”
Section: Figurementioning
confidence: 99%